1972
DOI: 10.1002/1097-0142(197202)29:2<349::aid-cncr2820290214>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative radiotherapy on peripheral blood lymphocytes in patients with carcinoma of the breast

Abstract: The effect of prophylactic postoperative radiotherapy in patients with carcinoma of the breast was determined on cells in the peripheral blood. Controls had carcinoma of the breast treated by radical mastectomy. Results were also compared with those in patients with carcinoma of the cervix treated by radiotherapy. None had recurrent disease. Radiotherapy of carcinoma of the breast decreased the total white blood cell count by 15% during the period of the first 6 months but did not alter the granulocyte count. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1972
1972
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The two methods gave comparable results (Table I) (Meyer, 1970;McCredie, Inch and Sutherland, 1972) and reduced PHA induced blast transformation (Stjernsward et al, 1972) In the 7 day tests, 47% of patients reacted to autologous and 40% to allogeneic breast tumour antigens; 28/45 (62%) patients positive to autologous antigens also reacted to allogeneic tumour preparations, while only 7143 (16%) patients negative to autologous antigens cross-reacted with allogeneic tumours (P < 0-001, Chi-squared with Yates' correction). This might indicate that negative in vitro results truly indicated a lack of reactivity on the part of the patient and were not due to variations in the fractionation of tumours.…”
Section: Resultsmentioning
confidence: 88%
“…The two methods gave comparable results (Table I) (Meyer, 1970;McCredie, Inch and Sutherland, 1972) and reduced PHA induced blast transformation (Stjernsward et al, 1972) In the 7 day tests, 47% of patients reacted to autologous and 40% to allogeneic breast tumour antigens; 28/45 (62%) patients positive to autologous antigens also reacted to allogeneic tumour preparations, while only 7143 (16%) patients negative to autologous antigens cross-reacted with allogeneic tumours (P < 0-001, Chi-squared with Yates' correction). This might indicate that negative in vitro results truly indicated a lack of reactivity on the part of the patient and were not due to variations in the fractionation of tumours.…”
Section: Resultsmentioning
confidence: 88%
“…Although methods have varied and results differed, most workers agree that RT causes a decrease in the response to mitogens (5,(34)(35)(36)(37)(38). A few have found that RT does not effect the lymphocyte response to mitogens (37,39,40). The time after cessation of RT at which the mitogen stimulation is measured is crucial (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the impaired response in untreated patients appears to be due to a factor which interferes with the capacity of the circulating lymphocytes to form E rosettes and to respond adequately to PHA.2 We have recently been able to demonstrate such a factor in the serum and in extracts from the spleens of untreated patients with Hodgkin's disease,3 and to reverse the impaired responses of peripheral blood lymphocytes from these patients by overnight incubation in 20% fetal calf serum. 2 Lymphocyte stimulation by Con A was also impaired in both untreated patients and in patients in long term remission after radiotherapy (Fig. 2).…”
Section: Reversal Of Cell Surface Abnormalities Of T Lymphocytes Inmentioning
confidence: 89%
“…Radiation induced alterations in the number and function of peripheral blood lymphocytes have recently been described in patients treated with radiotherapy for carcinoma of the breast (1-6), lung (7)(8)(9), bladder (7)(8)(9)(10), uterine cervix (2,6,11). testicular seminoma and carcinoma (12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation